The role of the semantheme “Heart” in the structure of the field “Spiritual state” (based on the material of the Russian language) - Zamanova, Ilona (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article deals with the question of denotative space of spiritual state concepts, analyzes the semantic structure of the lexeme ‘Heart’, author makes attempts to reconstruct the semantheme ‘Heart’, what is based on the lexicographic dictionaries data, contexts usage and stable combinations. The nests of semanthems, where each semantic feature of the stratified complex was acted as dominant, are also analyzed. Thus at the level of language prototypes and at the level of implementation of these prototypes in the language an attempt to fully describe the structure of the semantheme “Heart” is complete. The author drew attention to the texts of the early historical era, where it was noticed that abstract concepts at the language level were denoted using the lexical block “Heart”, but at the present stage of language development all these concepts have a separate lexeme. This observation gave the author the opportunity to assert that the “Heart” is one of the first semanthems in the spiritual sector of the system “Man”. Based on the analysis, author is stated that in the hierarchy of the spiritual sector of the system “Man” semantheme ’Heart’ occupies a nuclear position, it is initial nominator of the specific reaction of the heart as an organ, later it spread the field of meaning in the direction of three other basic meanings – thoughts/feelings/desires, which gave the language consciousness the opportunity to build all subsequent abstract concepts, nuclear generalized features of the semantheme ’heart’ can be found in the semantic structure of the lexical units, nominating the sphere of spirituality. The study of the semantheme ‘Heart’ paved the way for the possibility of a new vision to the vocabulary of emotions and mental states in general denotative space. The author suggests including to the denotative space the assessment of the phenomenon by the participant, the intensity of the manifestation of the heart reaction, the intensity of desire, facial or effective reaction. It is proposed to specify the intensity using a scale with positive and negative indicators.